Ionic-Liquid-Based Aqueous Biphasic Systems Fundamentals and Applications - Freire, Mara G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book offers comprehensive information on the fundamentals and applications of ionic-liquid-based aqueous biphasic systems, which have predominantly (and successfully) been employed as alternative platforms for the extraction, separation and purification of diverse high-value products. The book consists of an initial introduction providing a brief overview, from fundamentals to applications, followed by nine chapters addressing the respective phase diagrams (interpretation and characterization) and remarkable examples of their applications. It also includes two final chapters focusing on recent developments in the search for more environmentally-benign and biocompatible ionic-liquid-based aqueous biphasic systems, and on the progress made to date concerning the recovery, recycling and reuse of the phase-forming components, the goal being the development of cost-effective and sustainable processes. The book offers an interesting and useful guide for a broad readership in the fields of green chemistry, biotechnology, chemical engineering, and biochemistry, among others. Mara G.Freire is a Coordinator Researcher at CICECO - Aveiro Institute of Materials, Chemistry Department, University of Aveiro, Portugal.
Introduction to ionic-liquid-based aqueous biphasic systems (ABS) -- ABS Composed of Ionic Liquids and Inorganic Salts -- ABS composed of ionic liquids and carbohydrates -- ABS composed of ionic liquids and polymers -- Extraction of Amino Acids with ABS -- Extraction of proteins with ABS -- Extraction of alcohols, phenols and aromatic compounds with ABS -- Extraction of Natural Phenolic Compounds with ABS -- Extraction of metals with ABS -- Surfactant self-assembly within ionic-liquid-based aqueous systems -- On the Hunt for More Benign and Biocompatible ABS -- Towards the recovery and reuse of the phase-forming components of ABS. .
Keywords: Biotechnology; Chemistry, Technical; Sustainability; Analytical chemistry; Chemical Bioengineering; Industrial Chemistry; Sustainability; Analytical Chemistry